Effect of intravenous ascorbic acid infusion on blood loss during laparoscopic myomectomy: a randomized, double-blind, placebo-controlled trial. (April 2016) - Lee, Banghyun; Kim, Kidong; Cho, Hye Yon; Yang, Eun Joo; Suh, Dong Hoon; No, Jae Hong; Lee, Jung Ryeol; Hwang, Jung Won; Do, Sang Hwan; Kim, Yong Beom
Abstract: Objective: Most interventions aimed at reducing bleeding during myomectomy lack sufficient evidence regarding their effectiveness. Recently, it was reported that intraoperative ascorbic acid administration effectively reduced blood loss during abdominal myomectomy. Therefore, this study aimed to investigate whether intravenous ascorbic acid infusion would affect intraoperative blood loss in women undergoing laparoscopic myomectomy. Study design: A randomized, double-blind, parallel-group, placebo-controlled trial including 50 women undergoing laparoscopic myomectomy was conducted. Women with ≤4 myomas, ≤9 cm in maximum diameter were eligible. The study:control group ratio was 1:1. Starting 30 minutes before anesthesia, 2 g of ascorbic acid or a placebo were administered for 2 hours intraoperatively. Intraoperative blood loss, the primary endpoint, was calculated as the difference between the volume of fluids acquired from suction and that used for irrigation of the abdominal cavity during surgery using constant values. Results: Among the 50 randomized women, 1 and 3 in the study and control groups, respectively, were excluded due to withdrawal of consent, cancelation of surgery, or non-measurement of the primary endpoint. The baseline and operative characteristics were similar between the study and control groups, as was the intraoperative blood loss (193 ± 204 mL vs. 159 ± 193 mL, P  = 0.52). In addition, the operating time (95 ± 29 min vs. 110 ± 52 min; P  = 0.50) and decrease in hemoglobin level after surgery (1.9 ± 1.31 g/dL vs. 1.4 ± 1.4 g/dL; P  = 0.24) were similar between the study and control groups. Conclusions: Intravenous ascorbic acid infusion did not reduce intraoperative blood loss in women undergoing laparoscopic myomectomy. Clinical trial registration: ClinicalTrials.gov, www.clinicaltrials.gov, NCT01715597 .